Right to Intimacy as an Expression of Feminism in the Works of Writer Manju Kapur - Rathore, Archana (International Journal of English Literature and Social Sciences (IJELS), 2019)
This paper analyses the right to intimacy and love in the novels of Indian writer Manju Kapur, considering it as a strong dimension of Feminism. Being bold and audacious enough to break the barriers of orthodox prudery, Manju Kapur gives voice to the hitherto subdued feminism in Indian English fiction. The twenty first century fiction firmament has seen the rise of certain brilliant stalwarts like Khaled Husseini and Paulo Coelho but when it comes to Indian writing in English, we find Jhumpa Lahiri, Kiran Desai and Manju Kapur, making a distinct place for themselves. But my focus is on Manju Kapur as she resides in India and especially because she has graduated with more poise and panache in the cosy canopy of intimacy in her last three novels. It is a psychologically proved fact that Intimacy is beneficial for individual health and well being. Individuals who perceive their spouses to be supportive confidantes are buffered from the pathogenic effects of stress. In contrast, people whose intimacy needs are not met feel lonelier (Rubenstein and Shaver 1982) and their relationships are more prone to dissolution (Hendrick 1981). Its course can be seen working in the marital journey of Astha and Hemant, Nina and Ananda, Virmati and Professor Harish and the families of Sona and Rupa. We have to look at intimacy from the marital point of view because of the socio-cultural context of India where Manju Kapur writes. “Even marriage, in the true religious sense of Holy Matrimony, does not depend on a romantic attraction to hold it together; instead it derives its meaning as an unbreakable act of family and societal service between a man and a woman to a mutual divine love.”3 But then peeping deep into the philosophy of intimacy and especially the politics of marital intimacy, we fathom how difficult it gets to achieve that much-idealised and over-hyped divine love as the stark individuality of both husband and wife starts coming to the fore. Hemant in A Married Woman is busier in his business of making TVs while Astha keeps pining for his attention. Similarly, Ananda in The Immigrant tries to camouflage his sexual impotency by being busy in his work, not realizing the fact that how much Astha missed Anand especially because he was his anchor in this country. Neena needed more of this intimacy as she left her career and her country for him. And no doubt things get aggravated when in a foreign country. She confesses, “I don’t know what I want. At home it was much clearer. I feel so lost here.’